PEMBUATAN GAME INDONESIA MERDEKA - William William (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Indonesia Merdeka games is an educational games that aims to increase knowledge about the history of struggle for independence on August 17, 1945. These games besides giving pleasure also provide knowledge of the history of Indonesian independence to the players. This game can only played on Windows operating system. Making games Indonesia Merdeka created using Adobe Flash software using Actionscript 3.0. this game consist of  10 episodes.  Each episodes has different games that sack races, tug of war, mounting nut, trivia quizzes, shooting games, and stealth game. After going thorugh the testing phase can be concluded that Indonesia Merdeka games already have good quality and has been running well. By playing the games player knowledge of independent Indonesia increases.